Concurrent beneficial (vitamin D production) and hazardous (cutaneous DNA damage) impact of repeated low‐level summer sunlight exposures3. (18th November 2016) - Felton, S.J.; Cooke, M.S.; Kift, R.; Berry, J.L.; Webb, A.R.; Lam, P.M.W.; de Gruijl, F.R.; Vail, A.; Rhodes, L.E.
Summary: Background: The concurrent impact of repeated low‐level summer sunlight exposures on vitamin D production and cutaneous DNA damage, potentially leading to mutagenesis and skin cancer, is unknown. Objectives: This is an experimental study (i) to determine the dual impact of repeated low‐level sunlight exposures on vitamin D status and DNA damage/repair (via both skin and urinary biomarkers) in light‐skinned adults; and (ii) to compare outcomes following the same exposures in brown‐skinned adults. Methods: Ten white (phototype II) and six South Asian volunteers (phototype V), aged 23–59 years, received 6 weeks' simulated summer sunlight exposures (95% ultraviolet A/5% ultraviolet B, 1·3 standard erythemal doses three times weekly) wearing summer clothing exposing ~35% body surface area. Assessments made were circulating 25‐hydroxyvitamin D [25(OH)D], immunohistochemistry for cyclobutane pyrimidine dimer (CPD)‐positive nuclei and urinary biomarkers of direct and oxidative (8‐oxo‐deoxyguanosine) DNA damage. Results: Serum 25(OH)D rose from mean 36·5 ± 13·0 to 54·3 ± 10·5 nmol L −1 (14·6 ± 5·2 to 21·7 ± 4·2 ng mL −1 ) in phototype II vs. 17·2 ± 6·3 to 25·5 ± 9·5 nmol L −1 (6·9 ± 2·5 to 10·2 ± 3·8 ng mL −1 ) in phototype V ( P < 0·05). Phototype II skin showed CPD‐positive nuclei immediately postcourse, mean 44% (range 27–84) cleared after 24 h, contrasting with minimal DNA damage and full clearance in phototype V ( P < 0·001). The findings did not differ from those following single ultraviolet radiation (UVR) exposure. Urinary CPDs remained below the detection threshold in both groups; 8‐oxo‐deoxyguanosine was higher in phototype II than V ( P = 0·002), but was unaffected by UVR. Conclusions: Low‐dose summer sunlight exposures confer vitamin D sufficiency in light‐skinned people concurrently with low‐level, nonaccumulating DNA damage. The same exposures produce minimal DNA damage but less vitamin D in brown‐skinned people. This informs tailoring of sun‐exposure policies. Abstract : What's already known about this topic? Repeated low‐level exposures to simulated U.K. sunlight can produce vitamin D sufficiency in light‐skinned people, but the concurrent impact on cutaneous DNA damage is unknown. What does this study add? Low‐level simulated sunlight exposures in people of skin phototype II conferred vitamin D sufficiency concurrently with DNA damage, which showed partial clearance at 24 h and no evidence of accumulated damage after 6 weeks of exposures. The same exposures produced minimal DNA damage but less vitamin D in brown‐skinned people (phototype V). The findings are informative for sun‐exposure guidance. Plain language summary available online